2022
DOI: 10.1101/2022.01.21.477211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promoting Fc-Fc interactions between anti-capsular antibodies provides strong immune protection against Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is the leading cause of community-acquired pneumonia and an important cause of childhood mortality. Despite the introduction of successful vaccines, the global spread of both non-vaccine serotypes and antibiotic-resistant strains reinforce the development of alternative therapies against this pathogen. One possible route is the development of monoclonal antibodies (mAbs) that induce killing of bacteria via the immune system. Here we investigate whether mAbs can be used to induce killin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
2
4
0
Order By: Relevance
“…In the presence of complement, uptake was greatly enhanced. This is in agreement with previous work on Streptococcus pneumoniae, where IgG1 mAbs directed against capsule polysaccharide CPS6 were completely dependent on complement deposition (24). In contrast, we previously observed that naturally occurring IgG, IVIG (45) and a monoclonal antibody against WTA (23) can induce Fc receptor mediated phagocytosis of S. aureus in absence of complement.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the presence of complement, uptake was greatly enhanced. This is in agreement with previous work on Streptococcus pneumoniae, where IgG1 mAbs directed against capsule polysaccharide CPS6 were completely dependent on complement deposition (24). In contrast, we previously observed that naturally occurring IgG, IVIG (45) and a monoclonal antibody against WTA (23) can induce Fc receptor mediated phagocytosis of S. aureus in absence of complement.…”
Section: Discussionsupporting
confidence: 93%
“…Hexamer enhancing mutations have already been shown to enhance complement mediated lysis of Neisseria gonorrhoeae (47) and tumor cells (26) via the formation of membrane attack complex pores. Together with data on S. aureus (23) and S. pneumoniae (24), our study provides an important proof of concept that hexamer enhancing mutations can also potentiate opsonization and phagocytic killing of Gram-positive bacteria. This indicates that hexamer enhancing mutations could be applied to a broad range of pathogens and diseases.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Antibodies with hexamerization-enhancing mutations (hexabodies) activate complement more efficiently compared to wild-type IgG. These hexabodies showed more efficient C3b activation and phagocytosis of Staphylococcus aureus in vitro, Streptococcus pneumoniae in vitro and more efficient MAC activation and bacterial lysis of Neisseria gonorrhoeae in vitro and in vivo (54)(55)(56). Recently, it was shown that hexabodies can also enhance C3b activation and phagocytosis of Staphylococcus epidermidis in the context of neonatal plasma in vitro (42).…”
Section: Modified Monoclonal Antibodiesmentioning
confidence: 99%